A Teoria do Capital Humano e o Ensino Superior: o Caso da Universidade Tecnológica Federal do Paraná - Bassaco, Áquilla Carolina Garcia (2024)
The subject of this research is the Federal Technological University of Paraná, a university that stands out among the other federal universities in Brazil for being one of the few universities that falls into the category of specialized university by field of knowledge, in the technological area. The investigative process of this research was guided by the following question: how does the Human Capital Theory, incorporated into the World Bank's guidelines for reforming higher education, materialize in UTFPR's institutional documents? The hypothesis that guided this research is that UTFPR, by organizing itself as a university specialized by field of knowledge in the technological area, since its inception, sought to meet the guidelines of international organizations, especially the World Bank, which advocated that higher education institutions in developing countries should meet the demands of the market, offering “shorter, lower cost” higher education courses that would equip future workers with knowledge and skills that would increase the productivity of workers, considered human resources in the production process. Based on a bibliographical survey of productions published by the World Bank, we tried to identify the guidelines for higher education and how they are intertwined with the Human Capital Theory, a theory developed by Schultz and propagated by the World Bank, especially in developing countries. To answer this question, we examined the process that culminated in the creation of UTFPR, trying to understand that, despite having the term “technological” in its name, the university differs little from its peers, the so-called classical universities. We analyzed the documents published by the World Bank referring to higher education and the theory of human capital and finally, we analyzed the official documents of UTFPR, trying to identify the presence of World Bank guidelines in these documents. This is a documentary and bibliographical study using primary and secondary sources (articles, book chapters, dissertations and theses). The results of this research show that, despite resistance from segments of the university community, the World Bank's guidelines are present in the university's institutional documents, which conceive of the institution's objective as responding to the demands of the productive sector, of capital, through teaching, research and extension activities.